A review of literature on the measurement of advertising effectiveness: Part ii: The post-display analysis of promotional effectiveness - Corkindale, David; Kennedy, Sherril (Cranfield School of Management, 1973)
The initial review of the MCRU - Report Number 2 - covers two main areas of concern:- Part i "The pre-display assessment of advertising" Part ii "Post display analysis of promotional effectiveness" The report will cover what are considered to be main issues in evaluating methods of measuring advertising efffectiveness, for this was the guise under which the project was orginally set up. At a later date it is intended that a further review should be published on the material concerned with the process of how advertising works. This obviously has a strong overlap with any discussion on evaluation of effectiveness, but the area is large enough to warrant its own paper. It should be noted that as other areas become more evident as being of particular interest to the sponsor companies, an attempt will be made to review any relevant information which is available.